Penerapan Kurikulum Komprehensif Montessori, Waldorf Dan Reggio Emilia Pada Desain Interior Kindergarten - Evelyn Two; Aghastya Wiyoso; Andrey Caesar Effendi (Prodi Arsitektur Universitas Matana, 2023)
Education is one of important aspect for everyone to have a better life, build a good character, both from nature or nurture, attitude and behaviour which becomes a strong grip and base for every individual to be able to live a social life among the community. In order for that, children from 0-5 years old which is in rapid growth phase commonly known as golden age they needs full attention of both parents because intelligence potential has been formed to absorb information and receive stimuli they get from the surrounding environment, and through this process, children sees their parents as role model. However, due to the pressure of hustle environment, some parents can’t give their full attention to their children. Therefore, educational institutions are needed to support the teaching and learning process with good facility and standardization. This design uses a method created by William M. Pena namely problem seeking with aims to propose an alternative Bambino Preschool interior design that uses 3 comprehensive curriculum, Montessori, Waldorf and Reggio Emilia with the application of the